AN ANALYSIS OF SHIFTS IN THE TRANSLATION OF ENGLISH PARTICIPIAL ADJECTIVES INTO INDONESIAN IN NOVEL “THE TWILIGHT SAGA: NEW MOON” - Herawati, Puput Septia; Suyudi, Ichwan; Setiarini, Ni Luh Putu (Journal of Language and Literature, 2016)
Shift means the small linguistic changes that occur in translating source text into target text. In this research, the writer analyzed shifts in the translation of English participial adjectives into Indonesian in novel “The Twilight Saga: New Moon”. The data, shifts of participial adjectives, were taken from a fiction novel “The Twilight Saga: New Moon” written by Stephenie Meyer and its Indonesian translation “New Moon: Dua Cinta” translated by Monica Dwi Chresnayani. The objectives of this research are: (1) to describe the kinds of English participial adjectives in novel “The Twilight Saga: New Moon”; (2) to elaborate the kinds of shifts in the translation of English participial adjectives in the novel; also, (3) to find out the most dominant shift found in the translation of English participial adjectives in the novel. Through this research which had been completed by qualitative method, the writer drew conclusions as: (1) There are two kinds of participial adjectives found in novel “The Twilight Saga: New Moon”, they are present participial adjectives and past participial adjectives. (2) There are three kinds of shifts which are found in the novel, namely structure shifts, class shifts, and unit shifts. From 100 (100%) data of present participial adjectives, there are 9 (9%) structure shifts, 57 (57%) class shifts, and 34 (34%) unit shifts. Meanwhile, there are 8 (18.18%) structure shifts, 10 (22.72%) class shifts, and 26 (59.09%) unit shifts from 44 (100%) data of past participial adjectives. (3) The most dominant shift found in the translation of English present participial adjectives in the novel is class shift that consists of 57 shifts or 57% of the data. Moreover, the most dominant shift found in the translation of English past participial adjectives in the novel is unit shift that consists of 26 shifts or 59.09% of the data.Keywords: shifts, translation, present participial adjectives, past participial adjectives